2019
DOI: 10.1016/j.afjem.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Access to acute care resources in various income settings to treat new-onset stroke: A survey of acute care providers

Abstract: Introduction Stroke affects 15 million people annually and is responsible for 5 million deaths per annum globally. In contrast to the trend in low- and middle-income countries (LMICs), stroke mortality is on the decline in high-income countries (HICs). Even though the availability of resources varies considerably by geographic region and across LMICs and HICs, evidence suggests that material resources in LMICs to implement recommendations from international guidelines are largely unmet. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This difference could however be explained by the fact that 20% of patients with a clinical diagnosis of an ischaemic stroke did not receive a CT scan – not an uncommon practice in resource challenged settings. Chunga et al reports that with regards to emergency access to imaging of the brain, 81% of LMICs had access to CT scans, with 84% of them having 24-h access to radiology services, compared to HICs with 83% and 98% respectively [ 19 ]. Global data on the availability of medical devices in 2014 estimated that the number of CT scan machines per 1 million population is only 0.32 in low-income centres compared with 42 in HIC and neuro-diagnostic tests are often inaccessible or unaffordable to many patients in LMIC settings [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference could however be explained by the fact that 20% of patients with a clinical diagnosis of an ischaemic stroke did not receive a CT scan – not an uncommon practice in resource challenged settings. Chunga et al reports that with regards to emergency access to imaging of the brain, 81% of LMICs had access to CT scans, with 84% of them having 24-h access to radiology services, compared to HICs with 83% and 98% respectively [ 19 ]. Global data on the availability of medical devices in 2014 estimated that the number of CT scan machines per 1 million population is only 0.32 in low-income centres compared with 42 in HIC and neuro-diagnostic tests are often inaccessible or unaffordable to many patients in LMIC settings [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the presence of prehospital EMS and EMS education on the LVO scale were associated with increased MT access on univariable models, but these were insufficiently answered to be included in additional analyses. Many LMIC lack a prehospital service or national emergency number 81 ; ambulances are either ill-equipped or lack trained personnel, or both 82,83 ; and patients prefer using their own vehicle for medical care. 84,85 Also, even in countries with an established prehospital system, the ambulances predominantly transport patients with trauma injuries and obstetric emergencies, and have a lower priority for acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 , 34 ] LMIC often have ineffective or immature prehospital services as well as a lack of a national emergency number, potentially contributing to a lower EMS utilisation rate. [20] The proportion of patients with symptoms of a stroke that are transported to hospital with EMS in HIC, however, are reported to be as high as 60%. [29] The median EMS call-to-hospital-arrival time in our study was 1 hour and 31 minutes, as opposed to 44 minutes reported in North West of England.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 , 18 ] These guidelines are however developed in HIC and are not feasible for resource challenged LMIC, where the severely ill and injured are still unable to access good quality prehospital and acute care. [ 15 , 19 , 20 ] Chunga et al. (2019) demonstrated that prehospital services and national emergency numbers were lacking in LMIC, along with significantly less access to specialist neurology and radiology services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation